Update on the Neuroimaging and Electroencephalographic Biomarkers of Epileptogenesis: A Literature Review - Chen, Guihua; Zhang, Zheyu; Wang, Meiping; Geng, Yu; Jin, Bo; Aung, Thandar (Frontiers in Neurology, 2021)
Epilepsy is one of the most common debilitating neurological disorders that lead to severe socio-cognitive dysfunction. While there are currently more than 30 antiseizure medications available for the treatment and prevention of seizures, none address the prevention of epileptogenesis that leading to the development of epilepsy following a potential brain insult. Hence, there is a growing need for the identification of accurate biomarkers of epileptogenesis that enable the prediction of epilepsy following a known brain insult. Although recent studies using various neuroimages and electroencephalography have found promising biomarkers of epileptogenesis, their utility needs to be further validated in larger clinical trials. In this literature review, we searched the Medline, Pubmed, and Embase databases using the following search algorithm: “epileptogenesis” and “biomarker” and “EEG” or “electroencephalography” or “neuroimaging” limited to publications in English. We presented a comprehensive overview of recent innovations in the role of neuroimaging and EEG in identifying reliable biomarkers of epileptogenesis.